DIMETHYL N-CYANODITHIOIMINOCARBONATE AND TRIPHENYLPHOSPHINE OXIDE METAL HALIDE COMPLEXES: MOLECULAR CRYSTAL ELUCIDATION (Journal of Engineering Studies and Research, 2022)
Two MX2 (M = Ni, Zn; X = Cl, Br) dimethyl N-cyanodithioiminocarbonate compounds and one CrCl2 triphenylphosphine oxide complex were isolated and elucidated by single crystal X-ray crystallography. NiCl2[(CH3S)2C═NC≡N]2 (1) features inversion-related hydrogen bonded dimers linked into chains interacting through C-H···Cl growing layers along [110] whose junction into a 3D structure is enabled by H-bonds. ZnBr2[(CH3S)2C═NC≡N]2 (2) also exhibits inversion-related H-bonded dimers. In contrast with 1, the structure of 2 comprises chains along [110], connected via C-H···Br and C-H···S into a 2D layer along [-110]. CrCl2(OPPh3)2 (3) obtaining undergone redox processes, oxidizing [CH3C(O)CH2PPh3]+ to form PPh3PO, and reducing Cr from CrVI to CrII. In the structure, each molecule is linked to height neighbors through H-bonds affording a 3D network.
Keywords: crystal, dimethyl N-cyanodithioiminocarbonate, Ni(II), Zn(II), Cr(II), redox process, 2D-structure, 3D-structure